THE CONCEPTUAL APPARATUS OF THE TERM "FINISHED GOODS" AS AN OBJECT OF ACCOUNTING - A. Kasich; V. Shara (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article studies scientific approaches to the definition of "finished goods"; properties and various characteristics of the finished goods, which, in the author’s opinion, affect to the term’s wording. identified generalized features of the concept and differences from the executed works and the rendered services. Described the features and the main differences the ways of production of finished goods in certain economy’s sectors and proved the necessity of taking into account the specific features during the approach to the concept of "finished goods" in various industries. Analyzed the common and distinctive features of international and national standards for the accounting of inventory, because in the conditions of globalization becomes important the necessity of their identity. investigated the components of enterprise accounting policies, such as evaluation of reserves and write-offs on trade, applied in different countries of the world, revealed a basic discrepancy, namely, the use of LiFO method, which is prohibited for use in Ukraine, which, however, is used almost in all the considered countries. On the basis of the conducted research the author’s definition of "finished goods".